INFORMATION NEEDS OF MUSHROOM CULTIVATORS IN UDHAM SINGH NAGAR DISTRICT OF UTTARAKHAND - ARPITA SHARMA* (The Journal of Research ANGRAU, 2021)
The study was conducted to identify the needs of the mushroom cultivators. Seven villages were selected randomly and 100 respondents were selected. A list of 10 major areas of needs in relation to improved package of practices of mushroom cultivation was prepared. The collection of information is completed by pre-tested questionnaire. The study revealed that majority of mushroom growers were middle aged (45 percent) and possess secondary education (37 percent). The major sources of information were cell phone and T.V and majority have access to WhatsApp (social media) on their phones. The overall need assessment depicted that the training required of the mushroom growers was high especially regarding cultivation of mushroom, crop management, spawn preparation and the other procedures.